1983
DOI: 10.1029/ja088ia12p10210
|View full text |Cite
|
Sign up to set email alerts
|

Possible observation of a disconnected magnetic structure in a coronal transient

Abstract: We present SMM coronagraph/polarimeter observations of the coronal transient of March 15-16, 1980, which show a bright front convex toward the sun propagating out through the corona at 175 km s -•. A fan-shaped bright region connecting this front to the inner corona collapses into a narrow bright ray over the next few hours. We interpret these observations as resulting from the disconnection of magnetic loops from the underlying prominencelike loop structures seen rising earlier in the event.Other similar "inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 22 publications
(10 reference statements)
0
39
1
Order By: Relevance
“…11 shows a classical three-part ("light-bulb") CME morphology in a coronagraph image. The low density "dark cavity" corresponds to the flux rope, while the brightest features are a dense prominence core and a frontal rim of coronal loops that pile up at the flux rope leading edge (Illing and Hundhausen 1983;Dere et al 1999;Gibson and Low 2000). The excess mass image in the right-hand panel of Fig.…”
Section: Connection Between Icmes and Cmesmentioning
confidence: 99%
“…11 shows a classical three-part ("light-bulb") CME morphology in a coronagraph image. The low density "dark cavity" corresponds to the flux rope, while the brightest features are a dense prominence core and a frontal rim of coronal loops that pile up at the flux rope leading edge (Illing and Hundhausen 1983;Dere et al 1999;Gibson and Low 2000). The excess mass image in the right-hand panel of Fig.…”
Section: Connection Between Icmes and Cmesmentioning
confidence: 99%
“…T hree-Part Structure of Magnetic Field About one-third of CMEs observed in white light at the solar limb have a classical three-part structure (Illing & Hundhausen 1983) (Fig. 2a).…”
Section: Formation Of Sigmoid-arcade Conðgurations Andmentioning
confidence: 99%
“…White-light coronagraph observations in the past decades have revealed that many CMEs display a characteristic threepart structure: a bright loop-like leading front (LF), a dark cavity underneath, and an embedded bright compact core (Illing & Hundhausen 1983). When a pre-CME structure lifts off from the associated source region, it can cause the expansion and successive stretching of the overlying magnetic field lines to form a CME.…”
Section: Introductionmentioning
confidence: 99%